Development of a finite element-based computer program to determine the CG and area/mass moments of inertia of solids of complicated geometries - Ng, Lucas Jian Yong (Nanyang Technological University, 2022)
This FYP (Final Year Project) deals with the development of a finite element-based computer program to determine the center of gravity (CG) and area/mass moments of inertia of solids of complicated geometries. The calculation of these properties is important in the design and analysis of engineering structure and components.